Desain Alat Pendeteksi Arah Kedatangan Dan Nama Kereta Api Berbasis Arduino Pada Perlintasan Sebidang - Sunaryo, Sunaryo; Hermanto, Wawan (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2017)
Transportation safety must be obeyed by all modes of transportation. The railroad crossing is one point that has the potential for conflict between railroad shares and road users. In accordance with applicable regulations, railroad facilities are prioritized when passing level crossings. In fact, road users often try to break the rules. This research aims to present alternative solutions to improve the safety of road users and railroad lines at cross section level. This research uses a method that begins with a literature study. Next through the design phase, the prototype stage and finally the testing phase. The results of this study are the prototype of the railroad direction detector and the identification of electronic-based railways by using an Arduino Microcontroller. The result shows an LCD board that can provide information to road users for the train's arrival direction and train name. With this information it is expected that road users are more concerned with safety and can be careful when passing a level crossing.